1999
DOI: 10.1557/jmr.1999.0187
|View full text |Cite
|
Sign up to set email alerts
|

Imprint and Fatigue Properties of Chemical Solution Derived Pb1–-xLax(ZryTi1–y)1–x/4O3 Thin Films

Abstract: We have investigated the effect of oxygen vacancies on imprint and fatigue behavior of the PLZT thin films. It is found that the compensation of oxygen vacancies with various dopant concentrations and electrode structures is an important process parameter in determining the tendency to imprint and fatigue. In the case of PLZT thin films, the voltage shifts related to imprint are attributed to the trapping of electrons at ionic defect sites such as oxygen vacancies near the film/electrode interface, the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Another origin of the voltage shift is related to the magnitude of polarization. 14 The polarization constitutes an electrostatic potential well that attracts the electronic charge carriers, where they are trapped at near interfacial defect sites. A larger remanent polarization represents a deeper potential well, and consequently the trapping of charge carriers is more effective.…”
Section: Methodsmentioning
confidence: 99%
“…Another origin of the voltage shift is related to the magnitude of polarization. 14 The polarization constitutes an electrostatic potential well that attracts the electronic charge carriers, where they are trapped at near interfacial defect sites. A larger remanent polarization represents a deeper potential well, and consequently the trapping of charge carriers is more effective.…”
Section: Methodsmentioning
confidence: 99%
“…In order to clarify the interfacial problem, the frequency dependence of complex dielectric constant for some compounds in PZT and (Bi 2 O 2 ) 2+ (A m−1 B m O 3m+1 ) 2− systems has been studied. A remarkable low frequency dielectric dispersion below T c was observed in thin film capacitors of PZT [18], BST [19][20][21], Sr x Bi y Ta 2 O 9 (SBT) [8], Bi 2 Ti 2 O 7 [9], and Bi 4 Ti 3 O 12 [10]. It has been shown that this phenomenon greatly affects the electrical properties of the capacitors.…”
Section: Introductionmentioning
confidence: 98%
“…They proposed that the BLT thin film exhibits a fatigue-free characteristic and large remanent polarization. However, even if the BLT thin film is free from fatigue and imprint to simple Pt electrodes, they can also see an interfacial (electrode/bulk) problem similar to Pb(Zr x Ti 1−x )O 3 (PZT) [18] and (Ba, Sr)TiO 3 * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of less-expensive base metals with high-κ dielectric is challenging. The high firing temperatures and oxidizing atmospheres necessary for synthesis and densification of many oxides can be detrimental to oxidationsensitive base metals, especially copper, whereas the reducing atmospheres that are favored by base metals can result in excessive defect concentrations and frustrated phase formation of the dielectric ceramic films [7,10]. These effects lead to unsatisfactory dielectric performance for practical applications.…”
Section: Introductionmentioning
confidence: 99%